2013
DOI: 10.1007/s00467-013-2432-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-binding protein: a potential marker of febrile urinary tract infection in childhood

Abstract: The results of this study suggest that the serum LBP concentration constitutes a reliable biologic marker for the diagnosis of a febrile UTI in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In fact, LBP knockout mice are dramatically more susceptible to gram-negative infections compared with controls ( 43 ). Clinical studies have demonstrated that LBP is a useful biomarker for various infectious and infl ammatory states (44)(45)(46)(47).…”
Section: Cell Culturementioning
confidence: 99%
“…In fact, LBP knockout mice are dramatically more susceptible to gram-negative infections compared with controls ( 43 ). Clinical studies have demonstrated that LBP is a useful biomarker for various infectious and infl ammatory states (44)(45)(46)(47).…”
Section: Cell Culturementioning
confidence: 99%
“…The LBP binds to LPS and other microorganism components leading to activation of the inflammatory response [ 25 ]. LBP serum levels have been proposed as a useful diagnostic marker in both urinary infections in children and atherosclerosis, as well as a prognostic marker in acute appendicitis [ 26 ]-[ 28 ]. Future studies are warranted to confirm LBP as meaningful diagnostic marker in closed pyometra.…”
Section: Discussionmentioning
confidence: 99%
“…The primary end point was evidence of microbial invasion evaluated after 5 days of supplementation and defined as 1 or more of the following: (i) positive conventional blood culture (blood cultures were read automatically using the BioMérieux BactAlert system [BioMérieux, Marcy L'Etoile, France]); (ii) evidence of microbial DNA in blood by polymerase chain reaction (PCR); (iii) plasma endotoxin level ≥0.5 endotoxin units/mL (50 pg/mL); or (iv) plasma level of lipopolysaccharide‐binding protein (LBP) ≥50 µg/mL . Blood samples were taken at the beginning of the trial, at the introduction of first enteral feeding, and when full enteral feeding was achieved (parenteral feeding was stopped when >75% of the patient's full nutrition requirement was tolerated enterally for a minimum of 24 hours).…”
Section: Methodsmentioning
confidence: 99%